2005
DOI: 10.1590/s0034-89102005000500001
|View full text |Cite
|
Sign up to set email alerts
|

Perfil da violência de gênero perpetrada por companheiro

Abstract: KeywordsWomen's health. Domestic violence. Community health services. Spouse abuse. Abstract ObjectiveTo investigate the prevalence and profile of gender violence (physical, psychological, and sexual) perpetrated against women by current or former intimate partners. Methods This is a cross-sectional study carried out at a primary healthcare unit in the city of Porto Alegre, Southern Brazil. Our sample comprised 251 women aged 18-49 years who attended the healthcare unit between October and November 2003. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1
62

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 8 publications
2
44
1
62
Order By: Relevance
“…Poucos estudos na literatura avaliaram a religião entre fatores analisados, um deles observou que 67% das mulheres que sofreram violência, independente do tipo de agressão, referiram a prática de religião católica 16 . Ao contrário, este estudo mostrou que a referência à religião protestante/evangélica foi maior para a violência psicológica e sexual, mas não para a violência física.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Poucos estudos na literatura avaliaram a religião entre fatores analisados, um deles observou que 67% das mulheres que sofreram violência, independente do tipo de agressão, referiram a prática de religião católica 16 . Ao contrário, este estudo mostrou que a referência à religião protestante/evangélica foi maior para a violência psicológica e sexual, mas não para a violência física.…”
Section: Discussionunclassified
“…Foi observada, neste estudo, maior prevalência de violência entre as mulheres de classes econômicas mais baixas, resultado similar a estudo nacional no qual 59% das mulheres de classes D e E referiram violência psicológica, enquanto 43% dessas mesmas classes referiram violência física 16 . Ressalte-se que não há estudos com mulheres de estratos mais elevados, porque as pesquisas normalmente são realizadas em UBS ou hospitais públicos frequentados pela população de menor renda.…”
Section: Referênciasunclassified
“…5,7,[13][14][15] The prevalence of physical and sexual violence in this study were, however, higher than those from other Brazilian studies. 10,19 This may have been because of differences in how the questionnaire was applied, thereby resulting in greater revelation, or because of the samples' size. Additionally, the data showed the high recurrence and severity of intimate partner violence.…”
Section: Discussionmentioning
confidence: 99%
“…Another similar study in Porto Alegre (Southern Brazil) found rates of 38% for physical violence and 9% for sexual violence by a partner. 10 In emergency services in Bahia, 19 46% of the users reported some episode of violence in their lifetimes, of which 36.5% was physical and 18.6% was sexual. Partners and former partners were responsible for 65.7% of physical aggression and 68.7% of sexual aggression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation